Experimental Study on the Shear Strength of Loess Modified by Microbial Precipitation Technology - Bing-Xia Wang; Li-Jun Shi; Jian-Hua Dong; Lu Wang; Wen-Tong Tian (Advances in Materials Science and Engineering)
The shear strength (vertical pressure 50, 100, 200, and 300 kPa) and soil structure of the remolded loess with different proportions of the microbial cementing solution were measured and observed by the direct shear test and scanning electron microscopy (SEM).The results showed: (1) the increase in the microbial cementation solution led to the transformation of the stress-shear displacement curve from strain hardening to strain softening, with the transition interval of 26%∼34%. (2) With the increase in the microbial cementation solution, the change of cohesion showed a trend of “M,” the inflection point of the microbial cementation solution was 14%, 22%, and 34%, while the internal friction angle showed a law of “W,” where the inflection points of the internal friction angle were about 14%, 30%, 34%, and 38%, respectively. In the range of 18%∼30%, the cohesion and internal friction angle increase with an increase in the microbial cementation solution.(3) The change of cohesion is affected by the microbial mineralization saturation and the joint action of the occurrence state of Ca2+ and HCO3- in the microbial cementation solution. The change of internal friction angle is affected by the soil particle contact, the existing form of calcium carbonate formed by microbial precipitation, pore morphology, yield, and other forces. (4) By means of SEM, the distribution morphology of the soil particles and the contact microscopic images of the loess samples modified by microorganisms with different proportions were further verified to further verify the macroscopic changes of the shear strength of the modified loess samples cemented by microorganisms with different proportions. It provides a theoretical basis for the improvement of loess soil structure characteristics by microorganism calcium carbonate precipitation technology.